Occurrence and source apportionment of organic pollutants in deep sediment cores of the Venice Lagoon. (March 2021) - Pizzini, Sarah; Morabito, Elisa; Gregoris, Elena; Vecchiato, Marco; Corami, Fabiana; Piazza, Rossano; Gambaro, Andrea
Abstract: In this study, recent and aged inputs of five classes of organic contaminants ( i.e. PCBs, OCPs, PCDD/Fs, PAHs, and n -Alkanes) were evaluated in eight deep sediment cores of the Venice Lagoon, collected along the path of a new waterway whose excavation is under evaluation by local authorities, to assess the environmental quality status of the area. Diagnostic indices were calculated for identifying pollutant distribution patterns and their major emission sources, whose relative contribution was quantified by a Positive Matrix Factorization source apportionment model. Sedimentary depth profiles highlighted higher contamination in the top layer, mainly related to ship traffic combustion and vehicular/industrial emissions from the mainland. Nevertheless, a significant level of pollution has been detected also in the deeper layers, probably due to the transport of particulate matter through the aquifers underlying the lagoon seabed. The results underlined the threat posed by the possible resuspension of pollutants in the water column during contaminated sediment dredging. Highlights: Recent and aged inputs of several organic pollutants in Venice Lagoon were assessed. Sedimentary depth profiles revealed higher pollution in the top layer of the cores. Surface contamination is related to ship traffic, industrial, and biogenic sources. Aquifers could play a key-role in the pollutant transport towards core deep layers. Sediments might resuspend contaminants in the water column during their dredging.